Nutritional evaluation using oesophageal cannulated sheep under silvipasture - BHATTA, RAGHAVENDRA; SANKHYAN, S K; SHINDE, A K; KARIM, S A (The Indian Journal of Animal Sciences, 2013)
Use of oesophageal cannulation for nutritional evaluation in grazing sheep has been described. Adult Malpura rams(5) were fixed with oesophageal cannula fabricated in the institute using polyethylene material. The animals were grazed on 3.5 ha silivipasture plot during lush season (August to September 1995). CP content of composite sample of pasture and that obtained by extrusa technique was 10.18 and 12.15% on DM basis. NDF,ADF, cellulose, hemicellulose and GE values were similar in both the techniques. Lignin was significantly higher in extrusa compared to composite sample. DMI estimated by composite and total tilecal collection was 1 265 glbr/day compared to 665 glbr/day in extrusa and total faecal collection method. DCP and DE intakes also showed similar trends. Average soil ingestion was 76.87 g/br/day amounting to 11.56% of DMI. The present study indicate that oesophageal cannulated sheep could be successfully used in grazing studies for estimation of DMI and plane of nutrition.